2015
DOI: 10.1016/j.ijmultiphaseflow.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Simulating air entrainment and vortex dynamics in a hydraulic jump

Abstract: The air entrainment characteristics of three separate Froude number hydraulic jumps are investigated numerically using an unsteady RANS, realizable k-ε turbulence model, with a Volume of Fluid treatment for the free surface. Mean velocity profiles, average void fraction, and Sauter mean diameter compare favorably with experimental data reported in literature. In all simulations, time-averaged void fraction profiles show good agreement with experimental values in the turbulent shear layer and an accurate repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 50 publications
2
25
0
1
Order By: Relevance
“…Witt et al [67] simulated the air entrainment characteristics of three Froude number hydraulic jumps using the realizable k − model, with VOF treatment for the free surface through 2D and 3D simulations. Velocity profiles, void fraction profiles, and Sauter mean diameter were compared to the experimental data from Murzyn et al [81], Liu et al [75], and Lin et al [84], among others.…”
Section: Reynolds-averaged Navier-stokes Approachmentioning
confidence: 99%
“…Witt et al [67] simulated the air entrainment characteristics of three Froude number hydraulic jumps using the realizable k − model, with VOF treatment for the free surface through 2D and 3D simulations. Velocity profiles, void fraction profiles, and Sauter mean diameter were compared to the experimental data from Murzyn et al [81], Liu et al [75], and Lin et al [84], among others.…”
Section: Reynolds-averaged Navier-stokes Approachmentioning
confidence: 99%
“…Moreover, experiments probe a point or a plane, the complete three-dimensional (3D) flow field is not available for analysis. Recent improvements in computing capabilities have rendered numerical simulation as a viable tool to analyse the hydraulic jump flow field [8][9][10][11][12][13][14].…”
Section: mentioning
confidence: 99%
“…Most of the earlier simulations on hydraulic jumps have been performed using Reynolds-Reynolds-Averaged Navier-Stokes (RANS) models [8][9][10][11]. Ma et al, [12] compared the performance of RANS and Detached-Eddy simulations (DES) in simulating hydraulic jumps. He reported that the DES model was superior than RANS in resolving the free surface features of hydraulic jumps.…”
Section: mentioning
confidence: 99%
“…Computational fluid dynamics (CFD) models have been used to model TDG exchange, mixing, and transport (Xiao-li et al, 2010 andWeber et al, 2004). However, the computational effort necessary to resolve the smallest bubbles responsible for mass transfer is prohibitive (Witt et al, 2015), and CFD models, in addition to methodologies used in the physically based TDG prediction models, require calibration of many equation coefficients specific to each case.…”
Section: Background and Introductionmentioning
confidence: 99%